1993
DOI: 10.1080/03079459308418955
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a bisphosphonate on bone volume and eggshell structure in the hen

Abstract: SUMMARYBisphosphonates, used in the prevention and treatment of osteoporosis, in man, can prevent bone loss in experimental models of osteoporosis in mammals. In egg-laying hens there is a high incidence of bone fractures which are due to osteoporosis. Alendronate, a bisphosphonate, was given to three groups of hens in mid-lay. Different doses of alendronate were given to each group and group 4 was a control. The birds were killed after 2 weeks of treatment. The hens receiving the highest dosage of alendronate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…ALN-L mice (n = 30) received doses of 40 μg/kg/dose, while ALN-H mice (n = 30) received doses of 1,000 μg/kg/dose. The low-dose and high-dose treatments were chosen to represent the high and low range of effective doses from previous studies [10,19]. VEH mice (n = 30) were injected twice weekly with a vehicle solution (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…ALN-L mice (n = 30) received doses of 40 μg/kg/dose, while ALN-H mice (n = 30) received doses of 1,000 μg/kg/dose. The low-dose and high-dose treatments were chosen to represent the high and low range of effective doses from previous studies [10,19]. VEH mice (n = 30) were injected twice weekly with a vehicle solution (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…Continued research in this field at the Roslin Institute will serve to highlight whether husbandry, nutritional and genetic factors share an equal load in the predisposition to this crippling condition. Work by Thorp et al (1993) demonstrated the effects of the addition of a bisphosphonate on bone volume and eggshell structure in the hen. The authors concluded that treatment with alendronate has a potential role in preventing trabecular bone loss during lay and that the shell response to the inclusion of the drug was dose dependent.…”
Section: Bone and Shellmentioning
confidence: 98%
“…Aminohydroxybutane bisphosphonate (Alendronate, Merck, Sharp and Dohme Research Laboratories) inhibits trabecular bone loss in immobilized (Thompson et al, 1990) and ovariectomised (Seedor et ah, 1991) rats. A recent study has established that Alendronate is pharmacologically activity in egg-laying hens and has the potential to reduce the incidence and severity of osteoporosis (Thorp et al, 1993d). In man, osteoporosis can be prevented by the maximisation and maintenance of peak bone volume (Bhalla, 1993).…”
Section: Adults Selected For Egg Productionmentioning
confidence: 99%
“…The lesion is morphologically characterised by an accumulation of chondrocytes that appear to be unable to differentiate past a prehypertrophic (transitional) stage. The altered expression of matrix proteins and cellular enzymes by these cells suggests that there is a malfunction of the variety of autocrine and paracrine factors that control chondrocyte differentiation (Farquharson et al, 1992;Thorp et al, 1993d). TGFrjß is produced by growth plate chondrocytes (Rosier et al, 1989) and may regulate chondrocyte differentiation (Seyedin et al, 1985;Gelb et al, 1990;ten Dijke et al, 1990).…”
Section: Field Type Conditionmentioning
confidence: 99%